ANALISIS PERAN KEUANGAN INKLUSIF TERHADAP PROFITABILITAS PERBANKAN SYARIAH DI INDONESIA - Novita Dwi Anggraeni; Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
Financial inclusion is a national strategy to encourage economic growth aimed at eliminating all forms of barriers that are price and non-price, to people’s access to financial services based on the enforcement of Presidential Regulation No. 82 of 2016. Islamic banking has great potential to contribute in realizing national Financial inclusion. This research is a study that uses quantitative methods. In the form of secondary data with documentation study techniques. Independent variables consist of the ratio of the number of offices per adult population times 100,000 (X1), the ratio of third party funds (DPK) per Gross Domestic Product (GDP) times 100 (X2), the ratio of financing per Gross Domesti Product (GDP) times 100 (X3) the ratio of UMKM financing per Gross Domestic Product (GDP) by 100 (X4), the independent variable is profitability (Y) measured based on Return on Asset (ROA). Data collection in the form of islamic banking statistics report for the monthly period from July 2015 to June 2020. Data analysis uses multiple linear regression tests. The results of multiple linear regression tests show that all independent variables namely the total of offices (X1), DPK (X2), financing (X3), and UMKM (X4) simultaneously affect the profitability of ROA (Y). Partially, the DPK per GDP (X2) ratio has a significant influence on profitability (Y). While the ratio of the total offices per adult population (X1), the ratio of financing per GDP (X3) and the ratio of UMKM per GDP (X4) did not have a partially significant effect on profitability (Y).